1992
DOI: 10.1139/m92-127
|View full text |Cite
|
Sign up to set email alerts
|

The symbiotic vesicle is a major site for respiration in Frankia from Alnus incana root nodules

Abstract: VIKMAN, P.-A. 1992. The symbiotic vesicle is a major site for respiration in Frankia from Alnus incana root nodules.Can. J. Microbiol. 38: 779-784.A technique was developed for preparation of Frankia symbiotic vesicles, free of hyphae. The symbiotic vesicles were isolated by isopycnic centrifugation of disrupted Frankia vesicle clusters prepared from root nodules of Alnus incana (L.) Moench. Activities in symbiotic vesicles were compared with activities in intact symbiotic vesicle clusters on a total protein b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…While vesicles formed in the free-living state are always round and non-septate, the shape and cellular location of vesicles formed in planta depends on the host plant genus (Baker and Mullin, 1992), indicating that here, vesicles represent a symbiosis-specific differentiation comparable to bacteroids in legume nodules. In addition to diffusion resistance, the fast respiration rate of Frankia vesicles suggests that metabolic consumption of O 2 also plays a role in O 2 -protection of nitrogenase (Vikman, 1992). In nodules of Datisca, Frankia forms lanceolate vesicles in radial orientation that form a ring around the central vacuole.…”
Section: Regulation Of O 2 Supply To the Microsymbiontmentioning
confidence: 99%
“…While vesicles formed in the free-living state are always round and non-septate, the shape and cellular location of vesicles formed in planta depends on the host plant genus (Baker and Mullin, 1992), indicating that here, vesicles represent a symbiosis-specific differentiation comparable to bacteroids in legume nodules. In addition to diffusion resistance, the fast respiration rate of Frankia vesicles suggests that metabolic consumption of O 2 also plays a role in O 2 -protection of nitrogenase (Vikman, 1992). In nodules of Datisca, Frankia forms lanceolate vesicles in radial orientation that form a ring around the central vacuole.…”
Section: Regulation Of O 2 Supply To the Microsymbiontmentioning
confidence: 99%
“…They contain cytochromes a, b, c, and o (Ching, Monaco & Ching, 1983) and show cyanidesensitive oxygen consumption that is not affected by salicylhydroxamic acid (Vikman & Huss-Danell, 1987fl), an inhibitor of the alternative respiration pathway in plant mitochondria. Although these activities could take place in hyphae as well as in vesicles in vesicle clusters, Vikman (1992) showed that purified vesicles from such clusters have high respiratory capacity.…”
Section: Carbon Metabolism In Nodulesmentioning
confidence: 99%
“…Respiration is one such process. It has not yet been possible to measure respiration rates in vesicles in situ, but when vesicle clusters from Alnus incana nodules were sonicated, the fraction of the homogenate that was enriched in vesicles showed high respiratory capacity (Vikman, 1992). Although respiration consumes Og, it also gives rise to radical formation, as does nitrogenase activity (Gallon, 1992).…”
Section: The Oxygen Problemmentioning
confidence: 99%
“…Respiration both consumes oxygen and provides energy and reducing compounds for nitrogen fixation. It has not been possible to measure actual respiration in vesicles in the nodule, but vesicles prepared from vesicle clusters had high capacity to respire exogenous substrates (Vikman 1992). Radicals are produced in both the respiratory chain and by nitrogenase itself (Gallon 1993).…”
Section: Discussionmentioning
confidence: 99%